Flexible Wearables for Plants - Qu, Chun‐Chun; Sun, Xu‐Yang; Sun, Wen‐Xiu; Cao, Ling‐Xiao; Wang, Xi‐Qing; He, Zhi‐Zhu (Small (Weinheim an der Bergstrasse, Germany), 2021)
The excellent stretchability and biocompatibility of flexible sensors have inspired an emerging field of plant wearables, which enable intimate contact with the plants to continuously monitor the growth status and localized microclimate in real‐time. Plant flexible wearables provide a promising platform for the development of plant phenotype and the construction of intelligent agriculture via monitoring and regulating the critical physiological parameters and microclimate of plants. Here, the emerging applications of plant flexible wearables together with their pros and cons from four aspects, including physiological indicators, surrounding environment, crop quality, and active control of growth, are highlighted. Self‐powered energy supply systems and signal transmission mechanisms are also elucidated. Furthermore, the future opportunities and challenges of plant wearables are discussed in detail. This work highlights and reviews the emerging applications of plant wearables together with their pros and cons from four aspects, containing physiological indicators, surrounding environment, crops quality, and active control of growth, respectively.